Optimasi Penerapan Metode Text Recognition Dalam Fitur Catatan Otomatis Berbasis Mobile - Mulyana, Dadang Iskandar; Yel, Mesra Betty; Rahmanto, Muhammad Dzaky (STIKOM Tunas Bangsa Pematangsiantar, 2023)
This study discusses the optimization of Machine Learning Kit Text Recognition in creating an automatic note feature based on mobile devices. Machine Learning Kit Text Recognition is used to recognize text captured from photos taken by users. In this study, a mobile application was developed to allow users to create automatic notes by taking pictures of documents or texts, which are then recognized and transformed into editable digital text. This feature can help users to create notes more quickly and easily, as well as avoid errors in manually typing the text. In addition, the test results show that Machine Learning Kit Text Recognition is capable of recognizing text with fairly high accuracy, effectively recognizing text from various texts and fonts, supporting uncommon languages, preserving user privacy, and being able to perform text recognition processes offline or with more efficient resources. Therefore, the automatic note feature can run well on mobile applications built using Machine Learning Kit Text Recognition technology.